“Eye on the big prize!”: Iconizing the Democratic Alliance in the Daily Sun - Siebörger, Ian; Adendorff, Ralph (Stellenbosch Papers in Linguistics Plus, 2023)
This article gives a snapshot view of how Mmusi Maimane’s rise to leadership in the Democratic Alliance (DA) in 2015 was reported on in the Daily Sun, South Africa’s biggest-selling national daily newspaper (South African Audience Research Foundation, 2016). Through analysis of a Daily Sun news article exemplifying trends in the positioning of the DA in the tabloid over the first half of 2015, the present study demonstrates how Maimane tried to align the DA around a new iconography (Tann 2010, 2013), centred on the values of “freedom”, “fairness” and “opportunity”. Moreover, the present study also shows how this purported transformation in the DA was treated with scepticism by the news article’s author, who iconizes the DA as incapable of transformation and effective governance. Fine-grained complementary Legitimation Code Theory (LCT) and Systemic Functional Linguistics (SFL) analyses were conducted on this news article. The LCT analysis shows how multiple voices in the news article create conflicting binary constellations, axiologically charged through various linguistic resources, including intertextual references. The analysis, using SFL’s Appraisal system (Martin & White 2005), shows how iconization is accomplished in the news article through evaluative language, coupled with intertextual references, grammatical metaphor and technicality to produce syndromes of meaning in the news article. Such iconization works, in this case, to reproduce an attitude of cynicism toward party politics in post-apartheid South Africa. This cynicism foreshadows Maimane’s ultimate lack of success in transforming the discourses of the DA.